The importance of clinical examination and reproductive evaluation of rams. - GOULETSOU (Π. ΓΚΟΥΛΕΤΣΟΥ) P.; LAINAS (Θ. ΛΑΪΝΑΣ) T.; FTHENAKIS (Γ. Χ. ΦΘΕΝΑΚΗΣ) G. C. (Journal of the Hellenic Veterinary Medical Society, 2018)
In this review paper the importance of the clinical examination of rams for fertility evaluation is reviewed. Initially, the procedure of the examination is presented in detail; subsequently, the various pathological findings that may be detected, are described and their consequences for the reproductive soundness of rams are discussed.